Askelpituuden ja kävelyn kadenssin yhteys toiminnalliseen tasapainoon ikääntyneillä henkilöillä - Salminen, Marika (2024)
Walking is one of the most important mobility skills for older adults, as it enables independent everyday life and participation in social activities. As a person ages, many people start to experience walking challenges, such as changes in walking speed, step length, cadence, and the shape of the step. In addition to this, balance also deteriorates with age, as age-related activity in the sensorimotor and neuromuscular systems makes it difficult to control static and dynamic balance. The purpose of this master's thesis was to find out the association between walking cadence and step length with functional balance among well-functioning older adults.